AN ECOLOGICAL TREATMENT METHOD FOR IFOSFAMIDE CONTAMINATED WASTE WATER RESULTING FROM ONCOLOGICAL THERAPY - ORDODI, Valentin; PANĂ, Ana-Maria; DUMITREL, Alina; HĂDĂRUGĂ, Daniel; TĂMAȘ, Andra; PODE, Vasile; TODEA, Anamaria; PĂUNESCU, Virgil; NEGRU, Șerban (Studia Universitatis Babeș-Bolyai Chemia, 2020)
Ifosfamide is a potent alkylating agent used to treat many forms of human cancer. Exposure to this substance for the long term even in small quantities has serious negative effects on human health and the environment. This study presents an ecological method of electrochemical inactivation of ifosfamide in an automatic laboratory installation. The neutralization process consists of ifosfamide electrochemical and chemical oxidation via reactive chlorine species generated in situ at the anode of the electrochemical reactor with asymmetric current densities. The neutralization efficiency of ifosfamide using this method is approximately 99% if the duration of the electrodegradation process under the presented conditions is 30 minutes.